Hubungan Kualitas Kehidupan Kerja Dengan Keterampilan Mengelola Kelas Guru Sekolah Dasar - Sri Marmoah; Markus Sujarwo (JTP - Jurnal Teknologi Pendidikan, 2019)
Quality of work-life is the employees’ feeling or perception of being comfortable with their work. The objective of the present study was to determine the quality of work-life, classroom management skill, and the relationship between the quality of work-life and classroom management skill to elementary school teachers. This study uses a quantitative-correlational approach. The research subjects were 29 teachers from Pambudi Luhur elementary school in Surakarta, consisting of 14 female and 15 male teachers. Data collection in this study used a rating scale. Data analysis using product moment formula with the SPSS version 12 for Windows. The resultsof the research show that there is a significant relationship (0.531) between the quality of work-life and classroom management skill of the elementary school teachers. This means that the higher the quality of work-life of the teacher's, the better skill of managing the classroom.